Suppressed Th17 Levels Correlate with Elevated PIAS3, SHP2, and SOCS3 Expression in CD4 T Cells during Acute Simian Immunodeficiency Virus Infection - Bixler, Sandra L. (American Society for Microbiology, 2013)
T helper 17 (Th17) cells play an important role in mucosal immune homeostasis and maintaining the integrity of the mucosal epithelial barrier. Loss of Th17 cells has been extensively documented during human immunodeficiency virus (HIV) and simian immunodeficiency virus (SIV) infections. The lack of effective repopulation of Th17 cells has been associated with chronic immune activation mediated by the translocation of microbial products. Using ex vivo analysis of purified peripheral blood CD4 T cells from SIV-infected rhesus macaques, we show that the suppression of interleukin-17 (IL-17) expression correlated with upregulated expression of negative regulatory genes PIAS3, SHP2, and SOCS3 in CD4 T cells. Suppressed Th17 expression was accompanied by elevated levels of soluble CD14 (sCD14) and lipopolysaccharide binding protein (LBP) in the plasma during early stages of infection. Plasma viral loads rather than sCD14 or LBP levels correlated with acute immune activation. Additionally, we observed a significant increase in the expression of CD14 on peripheral blood monocytes that correlated with IL-23 expression and markers of microbial translocation. Taken together, our results provide new insights into the early events associated with acute SIV pathogenesis and suggest additional mechanisms playing a role in suppression of Th17 cells.